2020
DOI: 10.1051/0004-6361/202037635
|View full text |Cite
|
Sign up to set email alerts
|

The LOFAR view of intergalactic magnetic fields with giant radio galaxies

Abstract: Context. Giant radio galaxies (GRGs) are physically large radio sources that extend well beyond their host galaxy environment. Their polarization properties are affected by the poorly constrained magnetic field that permeates the intergalactic medium on megaparsec scales. A low frequency (< 200 MHz) polarization study of this class of radio sources is now possible with LOFAR. Aims. Here we investigate the polarization properties and Faraday rotation measure (RM) of a catalog of GRGs detected in the LOFAR Tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 82 publications
(126 reference statements)
2
36
0
Order By: Relevance
“…The exception is the FR I radio galaxy J0621-5647 in the far south, at the same z as the cluster pair. Polarisation measurements of these GRGs could be interesting for rotation-measure studies of the magnetic fields in the double cluster region (Pratley et al 2013;Stuardi et al 2020). Finally, there are some other notable radio galaxies that show signs of interaction with the ICM of A3391-A3395, such as the wide-angle tail source F2 as well as the radio galaxy F1.…”
Section: Other Notable Radio Featuresmentioning
confidence: 98%
“…The exception is the FR I radio galaxy J0621-5647 in the far south, at the same z as the cluster pair. Polarisation measurements of these GRGs could be interesting for rotation-measure studies of the magnetic fields in the double cluster region (Pratley et al 2013;Stuardi et al 2020). Finally, there are some other notable radio galaxies that show signs of interaction with the ICM of A3391-A3395, such as the wide-angle tail source F2 as well as the radio galaxy F1.…”
Section: Other Notable Radio Featuresmentioning
confidence: 98%
“…completely depolarized), but would be present in data at a higher frequency, such as at 1.4 GHz in the NVSS (Vernstrom et al 2019). Recently, a depolarization study of LOFAR polarized sources found that they have a typical RM dispersion within the beam of <0.3 rad m −2 (Stuardi et al 2020). Therefore, any radio galaxy that is embedded in an environment with RM fluctuations larger than this on scales smaller than 20 arcsec will not be present in the LOFAR data, but can be detected at 1.4 GHz (for RM dispersions up to a few 10s of rad m −2 ).…”
Section: Numerical and Physical Limitationsmentioning
confidence: 99%
“…Gaensler et al 2004) and associated advanced analysis techniques (e.g. Vernstrom et al 2019;O'Sullivan et al 2020;Stuardi et al 2020) might effectively probe such material. The thermal electron density drops rapidly with cluster-centric radius in typical ICM models, and the efficiency of Bremsstrahlung as a tracer of this gas drops more precipitously, since its emissivity is proportional to n 2 e .…”
Section: The Rm Grid As a Sensitive Tracer Of 'Missing' Baryons?mentioning
confidence: 99%